Measuring the impact of non‐monetary incentives on facility delivery in rural Zambia: a clustered randomised controlled trial. Issue 4 (April 2016) - Wang, P.; Connor, A. L.; Guo, E.; Nambao, M.; Chanda‐Kapata, P.; Lambo, N.; Phiri, C.
Abstract: Objectives: In Zambia, only 56% of rural women deliver in a health facility, and improving facility delivery rates is a priority of the Zambian government. 'Mama kit' incentives – small packages of childcare items provided to mothers conditional on delivering their baby in a facility – may encourage facility delivery. This study measured the impact and cost‐effectiveness of a US$4 mama kit on rural facility delivery rates in Zambia. Methods: A clustered randomised controlled trial was used to measure the impact of mama kits on facility delivery rates in thirty rural health facilities in Serenje and Chadiza districts. Facility‐level antenatal care and delivery registers were used to measure the percentage of women attending antenatal care who delivered at a study facility during the intervention period. Results from the trial were then used to model the cost‐effectiveness of mama kits at‐scale in terms of cost per death averted. Results: The mama kits intervention resulted in a statistically significant increase in facility delivery rates. The multivariate logistic regression found that the mama kits intervention increased the odds of delivering at a facility by 63% ( P ‐value < 0.01, 95% CI: 29%, 106%), or an increase of 9.9 percentage points, yielding a cost‐effectiveness of US$5183 per death averted. Conclusions: This evaluation confirms that low‐cost mama kits can be a cost‐effective intervention to increase facility delivery rates in rural Zambia. Mama kits alone are unlikely to completely solve safe delivery challenges but should be embedded in larger maternal and child health programmes.